Curcumin Protects Against Radiotherapy-Induced Oxidative Injury to the Skin - Shabeeb D; Musa AE; Abd Ali HS; Najafi M (Dove Medical Press, 2020)
Dheyauldeen Shabeeb,1,2 Ahmed Eleojo Musa,3 Hayder Shabeeb Abd Ali,4 Masoud Najafi5 1Department of Physiology, School of Medicine, University of Misan, Misan, Iraq; 2Misan Radiotherapy Center, Ministry of Health, Misan, Iraq; 3Department of Medical Physics, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Physiology, Ministry of Education, Misan, Misan, Iraq; 5Department of Radiology and Nuclear Medicine, Kermanshah University of Medical Sciences, Kermanshah, IranCorrespondence: Dheyauldeen ShabeebDepartment of Physiology, School of Medicine, University of Misan, Misan, IraqTel +9647717879332Email zahamtop5@gmail.comAhmed Eleojo MusaDepartment of Medical Physics, Tehran University of Medical Sciences, Tehran, IranTel +989012843317Email musahmed@yahoo.comObjective: Side-effects to normal tissues reduce the therapeutic window of radiotherapy. During radiotherapy, the skin is inevitably exposed to doses of ionizing radiation, leading to varying degrees of skin damage. Natural antioxidants have been explored for their radioprotective potentials. Thus, the present study aimed to investigate the protective effect of curcumin against radiotherapy-induced oxidative damage to the skin.Methods: Forty rats were divided into four groups as follows: vehicle control (without irradiation or drug treatment), treatment with 150 mg/kg curcumin, 10 Gy single dose irradiation only, and 150 mg/kg curcumin plus 10 Gy radiation (RC). In the treatment groups, each rat was treated orally with 150 mg/kg curcumin 1 day before irradiation to 3 consecutive days after irradiation. Weeks 1, 2, or 4 after irradiation, all rats were sacrificed and their skin tissues collected and frozen at − 80°C for the determination of malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activity in skin tissues.Results: Radiotherapy-induced oxidative injury to the skin was evidenced by elevated MDA levels as well as depleted CAT, SOD, and GSH-Px activities. However, the administration of curcumin before and after irradiation prevented radiotherapy-induced oxidative damage by significantly elevating the activities of antioxidant enzymes.Conclusion: From the findings of the present study, curcumin showed potential for protection against radiotherapy-induced oxidative injury to the skin. However, future studies are required to evaluate its clinical efficacy.Keywords: curcumin, radiotherapy, ionizing radiation, radiation protection, skin